1991
DOI: 10.1007/bf00142668
|View full text |Cite
|
Sign up to set email alerts
|

Clinical electrophysiology of the retinal pigment epithelium

Abstract: There is no ideal electrophysiological test for retinal pigment epithelial (RPE) function. The light-induced responses (EOG, c-wave, fast oscillation) that require photoreception are not pure RPE signals, and even the widely-used EOG has not been associated with any specific physiological disturbance of the RPE or retina. The discovery of non-photic RPE responses (hyperosmolarity, acetazolamide and bicarbonate) has enhanced the possibility of finding tissue-specific RPE tests, but these responses have yet to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…In addition, intra-individual variations in Li-EOG from normal subjects are also wide [25][26][27], thereby making it difficult to use for assessing changes in a single patient (unless a series of recordings were to be done). It may be time to re-evaluate the clinical utility of Li-EOG, not only relative to its few disease correlations beyond Best dystrophy [6] (e.g. ADVIRC [34], which is another bestrophin disease, and the staging of AZOOR [35]), but to its inter-and intra-individual variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, intra-individual variations in Li-EOG from normal subjects are also wide [25][26][27], thereby making it difficult to use for assessing changes in a single patient (unless a series of recordings were to be done). It may be time to re-evaluate the clinical utility of Li-EOG, not only relative to its few disease correlations beyond Best dystrophy [6] (e.g. ADVIRC [34], which is another bestrophin disease, and the staging of AZOOR [35]), but to its inter-and intra-individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several stimulating agents have been used, including hyperosmolar fluids, acetazolamide and sodium bicarbonate. However, these non-photic responses, much as the light EOG response, have shown clinical variability and no specific correlation with most diseases involving the RPE [6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it has been reported that disorders that include severe RPE abnormalities (such as rubella retinopathy and diffuse drusen) are not associated with changes in RPE electrophysiology, as evidenced by normal or mildly affected electrooculogram and nonphotic responses (Gupta and Marmor 1994;Marmor 1991). Each dc-ERG component reflects the activity of ion channels that undoubtedly play many roles in maintaining retinal homeostasis.…”
Section: It Is Not Clear Why Müller and Rpe Cell Responses Are Sparedmentioning
confidence: 99%
“…Chez les espèces nocturnes, l'état d'adaptation à l'obscurité sera obtenu au bout de plusieurs heures (BEHN et al, 2003). En ce qui concerne l'état d'adaptation à la lumière chez l'homme et les espèces animales diurnes, il est considéré comme stable au bout de deux heures, si la rétine a préalablement été exposée un temps très long à l'obscurité (MARMOR, 1991). Néanmoins, en pratique, on peut considérer que si l'éclairement rétinien est constant et uniforme pendant 10-15 minutes, il est possible d'obtenir un état d'adaptation photopique stable (GOURAS et MACKAY, 1989).…”
Section: L'état D'adaptation Rétinien Préalable à La Stimulationunclassified